Analisis Preferensi Masyarakat Dalam Pemilihan Lokasi Perumahan di Kelurahan Antang Kota Makassar - A.Dhita Maulya Pratiwi; Nurul Istiqamah Ulil Albab; Asmuliany Andi (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2026)
Antang Village, as part of Panakkukang District in Makassar City, is experiencing rapid development in the residential sector. This study aims to analyze the main factors that influence people's preferences in choosing housing locations in the region. The methods used include qualitative and quantitative analysis based on field data, literature studies, and document studies related to spatial planning and settlement development. The results of the study show that accessibility factors to the city center and public facilities, the availability of basic infrastructure (roads, drainage, electricity, and clean water), environmental security, affordable land prices, and land ownership certification are the main considerations of the community. In addition, the existence of planned housing such as Bukit Baruga also shapes the pattern of people's preferences for organized and exclusive housing. This study concludes that the preferences of the people in Antang Village are not only based on economic aspects, but also on social, environmental, and comfortable life aspects. These findings are expected to be input for developers and local governments in designing spatial policies and sustainable settlement development